2006
DOI: 10.1038/sj.onc.1209962
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of protein phosphatase 2A nuclear accumulation and subsequent inactivation of activator protein-1 in leptomycin B-inhibited cyclin D1 expression

Abstract: Leptomycin B (LMB) is a Streptomyces metabolite that causes the specific inhibition of the nuclear export of proteins containing a nuclear export signal (NES). LMB was reported to inhibit cell cycle progression in fission yeast and mammalian cells, however, the mechanism underlying LMB-induced cell cycle arrest is still obscure. In this study, we found that in serum-starved NIH3T3 cells, LMB inhibited serum-induced cyclin D1 expression at the level of transcription. However, this inhibition was reversed by inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…PP2A has been implicated in cellular growth control primarily based on the discovery that okadaic acid, an inhibitor of PP2A activity, is a potent tumor promoter (9). Whereas the mechanism underlying this observation remained elusive, it was shown that PP2A suppression leads to activation of the mitogen-activated protein kinase pathway in the absence of growth factor-initiated signaling, whereas PP2A is inactivated in response to cell growth stimulation (9,49). Additionally, certain oncoproteins interact with PP2A, thus impairing its function (9), and specific PP2A complexes have been found to be up-regulated in transformed cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…PP2A has been implicated in cellular growth control primarily based on the discovery that okadaic acid, an inhibitor of PP2A activity, is a potent tumor promoter (9). Whereas the mechanism underlying this observation remained elusive, it was shown that PP2A suppression leads to activation of the mitogen-activated protein kinase pathway in the absence of growth factor-initiated signaling, whereas PP2A is inactivated in response to cell growth stimulation (9,49). Additionally, certain oncoproteins interact with PP2A, thus impairing its function (9), and specific PP2A complexes have been found to be up-regulated in transformed cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…SCADS inhibitor kits I to III were kindly provided by the Screening Committee of Anticancer Drugs in Japan (28,29). For further characterization after screening, rapamycin (WAKO), KT5823 (WAKO), Akt Inhibitor VIII (Merck), actinomycin D (WAKO), and trichostatin A (WAKO) were used.…”
Section: Methodsmentioning
confidence: 99%
“…To identify signaling factors that potentially contribute to the regulation of MT1-MMP/ Mint3-dependent HIF-1 activation, we screened a panel of 252 well-characterized signaling inhibitors (28,29) by using a luciferase reporter assay to monitor the FIH-1-dependent HIF-1␣ activity in HT1080 cells (Fig. 1A).…”
Section: Screening For Inhibitors Of Mt1-mmp/mint3-mediated Posttransmentioning
confidence: 99%
“…Tsuchiya et al (21) reported a potential NES in the C-subunit although individual sequences were not tested for export function. We investigated the possible role of B56␣ in regulating C-subunit localization, given that transiently expressed B56␣ is known to associate with the C-subunit (7).…”
Section: Identification Of Critical Residues In the B56␣ Nes And Evidmentioning
confidence: 99%